IMMU-38. DEEP IMMUNOPROFILING OF HUMAN GLIOBLASTOMA (GBM) REVEALS DIFFERENCES IN THE TUMOR IMMUNE CELL INFILTRATE IN PATIENTS WITH HIGH VS. LOW PLASMA CELL-FREE DNA (CFDNA). (12th November 2021) - Bagley, Stephen J; Alanio, Cecile; Till, Jacob; Abdalla, Aseel; Binder, Zev; Desai, Arati; Brem, Steven; O'Rourke, Donald M; Carpenter, Erica; Wherry, E John
Abstract: BACKGROUND: We have previously demonstrated that high baseline plasma cfDNA concentration is associated with poor survival in patients with newly diagnosed GBM. The mechanism of this association remains unknown. To explore whether differences in the immune landscape between high- vs. low-cfDNA patients may play a role in their divergent clinical outcomes, we phenotyped tumors from patients with high vs. low cfDNA using mass cytometry by time of flight (CyTOF). METHODS: We performed CyTOF on frozen tumor infiltrate suspension from a pilot cohort of patients with previously untreated GBM with known baseline plasma cfDNA concentration (Bagley, Clin Cancer Res 2020). CyTOF was used to simultaneously measure expression of 39 molecules related to immune cell lineage, differentiation state, and function. Differences in immune cell infiltrates between high- and low-cfDNA patients were assessed using Mann-Whitney U tests. RESULTS: Four patients with high cfDNA (median 57, range 33-90 ng/mL) were compared to six patients with low cfDNA (median 12, range 7-16 ng/mL). Immune cell infiltrates with increased adaptive cells (high monocytes and T cells, p=0.05) were present in high-cfDNA compared to low-cfDNA patients. While > 70% of the infiltrating T cells were exhausted in both groups, the pattern of exhaustion was significantly different in high- vs. low-cfDNA patients, with less CXCR5+CD69+ and more CXCR5-CD69- (p=0.008) progenitor exhausted T cells in cfDNA-high patients. CONCLUSIONS: In this GBM pilot study, we demonstrated differences in the tumor immune infiltrate in patients with high vs. low baseline plasma cfDNA concentration. Preclinical studies will be needed to determine if this explains the association between high plasma cfDNA and poor outcomes previously observed in patients. Our results may have implications for the use of cfDNA concentration as a predictive biomarker for immunotherapy, as tumors with more intermediate progenitor (CXCR5-CD69-) exhausted T cells may respond better to PD-1 checkpoint blockade.